Vapour-bubble nucleation and dynamics in turbulent Rayleigh–Bénard convection. (13th April 2016) - Narezo Guzman, Daniela; Frączek, Tomasz; Reetz, Christopher; Sun, Chao; Lohse, Detlef; Ahlers, Guenter
Abstract : Vapour bubbles nucleating at micro-cavities etched into the silicon bottom plate of a cylindrical Rayleigh–Bénard sample (diameter D=8.8 cm, aspect ratio ΓD/L1.00 where L is the sample height) were visualized from the top and from the side. A triangular array of cylindrical micro-cavities (with a diameter of 30 μm and a depth of 100 μm ) covered a circular centred area (diameter of 2.5 cm) of the bottom plate. Heat was applied to the sample only over this central area while cooling was over the entire top-plate area. Bubble sizes and frequencies of departure from the bottom plate are reported for a range of bottom-plate superheats T_b-T_on ( T_b is the bottom-plate temperature, T_on is the onset temperature of bubble nucleation) from 3 to 12 K for three different cavity separations. The difference T_b-T_t16 K between T_b and the top plate temperature T_t was kept fixed while the mean temperature T_m=(T_b+T_t)/2 was varied, leading to a small range of the Rayleigh number Ra from 1.4× 10^10 to 2.0× 10^10 . The time between bubble departures from a given cavity decreased exponentially with increasing superheat and was independent of cavity separation. The contribution of the bubble latent heat to the total enhancement of heat transferred due to bubble nucleation was found to increase with superheat, reaching up to 25 %. The bubbly flow was examined in greater detail for a superheat of 10 K and Ra1.9× 10^10 . The condensation and/or dissolution rates of departed bubbles revealed two regimes: the initial rate was influenced by steep thermal gradients across the thermal boundary layer near the plate and was two orders of magnitude larger than the final condensation and/or dissolution rate that prevailed once the rising bubbles were in the colder bulk flow of nearly uniform temperature. The dynamics of thermal plumes was studied qualitatively in the presence and absence of nucleating bubbles. It was found that bubbles enhanced the plume velocity by a factor of four or so and drove a large-scale circulation (LSC). Nonetheless, even in the presence of bubbles the plumes and LSC had a characteristic velocity which was smaller by a factor of five or so than the bubble-rise velocity in the bulk. In the absence of bubbles there was strongly turbulent convection but no LSC, and plumes on average rose vertically.